Heavy Metals Configuration in Different Saprobic Level of Water Bodies - Lestari Lakhsmi Widowati; Restiana Wisnu Ariyati; Sarjito Sarjito; Sri Rejeki (University of Diponegoro, 2023)
The environmental conditions for aquaculture needs to be done in line with pollution that occur in waters which is categorized by saprobic index. The heavy metals content in cultured organisms present in the different levels of saprobity was informed by geospatial analysis through the overlay method. The Pb, Cd and Cr content were taken from tissues of milkfish, wild white shrimp and vaname shrimp. An Ikonos satelite Imagery data of Semarang used for geospatial analysis. The research was carried out from June to October 2021 in the brackish water ponds At Tugu district, Semarang, Central Java. The level of saprobity reported in oligosaprobic up to β-mesosaprobic which means lightly polluted to heavily polluted. The content in the water bodies (mg/L) of Pb 0.046 to 0.105, Cd 0.033 to 0.062 and Cr from 0.018 to 0.054 has exceeded the permittable level. Meanwhile, in the pond sediment (mg/kg) : Pb 3.56-6.93; Cr 1.08-3.01 is within permittable limits, however, Cd 1.77-3.53 has exceeded permittable levels. The content of heavy metals (mg/kg) in the tissues of milkfish, wild shrimp and white leg shrimp (L. vannamei): Pb 0.27 to 0.39, Cr 0.16 to 0.23 and Cd from 0.12 to 0.22 is still within permittable limits